ANTI-ULCEROGENIC ACTIVITY OF THE METHANOL ROOT BARK EXTRACT OF COCHLOSPERMUM PLANCHONII (HOOK f) - Ezeja, Maxwell I.; Anaga, Aruh O. (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
Cochlospermum planchonii (Hook f) is a common medicinal plant used in Nigeria traditional medicine for treatment of different ailments including ulcers. The anti ulcer activity of the root bark methanol extract of Cochlospermum planchonii was evaluated using different [ethanol, acetylsalicylic acid (aspirin), cold/restraint stress and pyloric ligation/histamine – induced ulcers and acid production] ulcerogenic models in rats at the doses of 250, 500, and 1000 mg/kg body weight using cimetidine (100 mg/kg) as a standard reference drug. The different doses of the extract and the reference drug significantly (p < 0.01) decreased all the ulcer parameters in a dose dependent manner in all the models used. The total number of ulcers were significantly (p < 0.05) decreased. The ulcer index was significantly (p < 0.004) reduced by the extract. Similarly, the percentage ulcer preventive index was also increased from 0% in the negative control up to 93.2% at the dose of 1000 mg/kg, while the percentage ulcer severity was dose dependently reduced by the extract. Furthermore, the extract significantly (p < 0.02) decreased free gastric HCl and total gastric acid. In conclusion, Cochlospermum planchonii methanolic root bark extract showed significant antiulcer activity in this study which may be as a result of its cytoprotective, antioxidant or antisecretory properties.